A BRIEF SUMMARY OF THE BERBERRY STUDY (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This article is about studying the Barberry species. information is given about the various views of researchers, in a literary presentation.
Keywords: Barberry, biology, ecology. genus, species, inflorescences, fruit, seed, introduction, morphogenesis.